Development of a Creative Economy for Shallot Farmers to Enhance Household Income in Sumberkedawung, Probolinggo - Muhammad Farid; Moch Mahsun; Indra Hidayatullah; Muhammad Masyhuri; Aang Burhanuddin; Siti Nur Latifah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Islam Syarifuddin Lumajang, 2025)
Sumberkedawung village, particularly the hamlets of Sempol and Kedungminian, is an agrarian area where shallots constitute the primary commodity and serve as a major driver of the local economy. Despite this potential, the shallot sector has not fully translated into improved farmer welfare due to several persistent challenges, including unstable market prices, limited financial capital, the absence of subsidised fertilisers, insufficient technical assistance from farmer groups and agricultural agencies, and weak post-harvest creative management. This study and community engagement programme employed a Participatory Action Research (PAR) approach, comprising several stages: general mapping, thematic mapping, transect walks, Focus Group Discussions (FGDs), problem- and objective-tree analyses, and the formulation of community-approved action plans. The principal intervention involved organising a seminar entitled “Creative Economy Development for Shallot Farmers to Improve Community Income in Sumberkedawung Village”, involving farmers and leaders of local farmer groups. The programme successfully encouraged a shift in farmers’ mindsets from relying solely on selling raw produce toward embracing value-added processing and developing high-quality shallot seed enterprises. These initiatives opened new opportunities for more stable and sustainable income generation. By the conclusion of the programme, the community demonstrated enhanced understanding of agricultural management and the potential of creative economic strategies, and formulated recommendations for developing processed shallot-based products as a pathway to improving the socio-economic well-being of farming households.